Utilization of a Conceptual Model in Projects Observatories Development: A Case Study - Vieira, Jeferson K. M.; Farias Junior, Ivaldir H. de; Moura, Hermano P. de (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2026: Anais do XXII Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2026.248335, 2026)
Research Context: Observatories are information systems that support project monitoring, providing transparency and decision-making support through data collection, processing, storage, and dissemination. Despite their potential, the practical application of conceptual models for project observatories remains limited. Scientific and/or Practical Problem: The third version of the Model for Project Observatories (MPO) had not been assessed in real-world contexts, raising questions about its applicability, completeness, and usability. Proposed Solution and/or Analysis: This study evaluates the MPO through two multiple-case studies, examining the application of its concepts, identifying gaps, and suggesting improvements, with emphasis on usability aspects. Related IS Theory: The MPO builds on a sociotechnical perspective and relates to theories of conceptual modeling and project management support systems, highlighting transparency and governance in information systems. Research Method: A multiple-case study was conducted, following a qualitative approach. Data were collected through interviews, participant observation, document analysis, and source code review, allowing the assessment and refinement of the model. Summary of Results: The results show that most MPO concepts were successfully applied. Some concepts were only partially incorporated, and new elements were suggested to enhance usability. Cross-case analysis provided insights into strengths and limitations of the model. Contributions and Impact to IS area: This study empirically validates and refines the MPO, reinforcing its role as a conceptual foundation for project observatories. It contributes to the IS field by demonstrating the use of observatories as tools for transparency and project management, and by offering guidelines for the effective implementation of conceptual models.